2004
DOI: 10.1074/jbc.m405509200
|View full text |Cite
|
Sign up to set email alerts
|

A Cooperative Role for Atf1 and Pap1 in the Detoxification of the Oxidative Stress Induced by Glucose Deprivation in Schizosaccharomyces pombe

Abstract: In Schizosaccharomyces pombe, glucose concentrations below a certain threshold trigger the stress-activated protein kinase (SAPK) signal transduction pathway and promote increased transcription of Atf1-dependent genes coding for the general stress response. Removal of glucose specifically induces the nuclear accumulation of green fluorescent protein-labeled Pap1 (GFP-Pap1) and the expression of genes dependent on this transcription factor. In contrast, depletion of the nitrogen source triggers the SAPK pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 54 publications
2
66
0
Order By: Relevance
“…Therefore, the elevated expression of the fbp1 gene in ird mutants (Figure 2) might be because of a lack of glucose repression. In addition, the high resistance of ird mutants to oxidative stress might result from a lack of glucose repression because it is known that glucose depletion causes resistance to oxidative stress in S. pombe (Madrid et al, 2004;Roux et al, 2009). …”
Section: Ability To Escape Glucose Repression In Ird Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the elevated expression of the fbp1 gene in ird mutants (Figure 2) might be because of a lack of glucose repression. In addition, the high resistance of ird mutants to oxidative stress might result from a lack of glucose repression because it is known that glucose depletion causes resistance to oxidative stress in S. pombe (Madrid et al, 2004;Roux et al, 2009). …”
Section: Ability To Escape Glucose Repression In Ird Mutantsmentioning
confidence: 99%
“…Atf1 and Pap1 are known to be involved in the regulation of the cellular defense mechanism(s) against increasing oxidative stress in aerobically growing, glucose-depleted cells (Madrid et al, 2004). These transcription factors have been proposed to be activated under mild oxidative stress conditions in S. pombe (Quinn et al, 2002).…”
Section: Oxidative Stress Resistance Of Ird Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the expression level of the sty1 gene encoding MAPK Sty1p, which increases the expression of various stress-responsive genes through the activation of the Atf1p and Pap1p transcription factors in S. pombe (Madrid et al, 2004), both in ird11 and wild type cells. In this study, no significant increase was observed in sty1 expression in ird11 under the nonstressed condition, whereas the expression level of sty1 decreased in ird11 under the stressed condition.…”
Section: Activation Of Sty1 In Oxidative Stress-resistant Mutant Of Smentioning
confidence: 99%
“…Furthermore, the activity of Ght3 is optimal at low glucose concentration (0.2%), 2% D-gluconate, or 2% maltose. Recently, it was reported that glucose depletion or respiratory growth on nonfermentable carbon sources leads to an increased oxidative stress response (Chen et al, 2003;Madrid et al, 2004;Kim et al, 2006;Chen and Runge, 2009) and extends life span in S. pombe (Lin et al, 2002;Roux et al, 2009Roux et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%